Bioregulator application, agronomic efficiency, and quality of soybean seeds Aplicação de biorregulador, desempenho agronômico e qualidade de sementes de soja - Marizangela Rizzatti Ávila; Alessandro de Lucca e Braccini; Carlos Alberto Scapim; Leandro Paiola Albrecht; Telmo Antônio Tonin; Marcibela Stülp (Scientia Agricola, 2008)
The application of vegetal bioregulators has shown promising results, mainly in cultures that have already reached a high level of technology. Based on this context an experiment was carried out with the objective of evaluating agronomic traits of plants, such as yield and quality of seeds, produced by applying bioregulators to a soybean crop. For this purpose, the following treatments were carried out: before sowing - seed treatment (25, 50 and 75 mL for 100 kg-1 seeds); during sowing time - spraying on the sowing lines (pulverization onto the sowing lines) (50, 100 and 150 mL ha-1); between stages V5 and V6 (25, 50 and 75 mL ha-1); and the control - no treatment. Emergence speed, final seedling emergence, number of pods and seeds per plant, average height of plants, first pod insertion height, duration of the cycle, final stand, degree of plant layering, and the yield and weight of one thousand seeds were evaluated. The quality of seeds was evaluated based on germination, classification of seedling vigor, tetrazolium, health test and the quantity of oil and protein tests. The highest yield of grains, an increase of 92% as compared to the control, was obtained when using the product at a dose of 75 mL ha-1. The best quality seeds and the highest oil and protein content were obtained from seeds produced by plants whose seeds were treated before sowing time using the bioregulator (75 mL for 100 kg-1 seeds). A aplicação de bioreguladores vegetais tem apresentado resultados promissores, principalmente nas culturas que atingiram nível elevado de tecnologia. Com base nesse contexto, instalou-se um experimento, com objetivo de avaliar o desempenho agronômico das plantas, a produtividade e a qualidade das sementes produzidas com aplicação de biorregulador na cultura da soja. Para tal, realizaram-se os seguintes tratamentos: antes da semeadura, tratamento de sementes (25; 50 e 75 mL para 100 kg-1 de sementes); na semeadura, pulverização dirigida no sulco de plantio (50; 100 e 150 mL ha-1); entre os estádios V5 e V6, pulverização foliar (25; 50 e 75 mL ha-1) mais a testemunha sem tratamento. Avaliou-se a velocidade de emergência, emergência final das plântulas, número de vagens e de sementes por planta, altura média das plantas, altura de inserção das primeiras vagens, duração do ciclo, estande final, grau de acamamento das plantas, produtividade e massa de mil sementes; a qualidade das sementes por meio dos testes de germinação, classificação do vigor das plântulas, tetrazólio e sanidade. Foram avaliados, ainda, os teores de óleo e de proteínas nas sementes. A maior produtividade de sementes foi obtida com a aplicação foliar do produto na dose de 75 mL ha-1 com incremento superior a 92% em relação à testemunha. A melhor qualidade de sementes e os maiores teores de óleo e proteínas foram obtidos nas sementes oriundas de plantas que tiveram suas sementes tratadas antes da semeadura com 75 mL 100 kg-1 do bioregulador.